Implementación de un sistema de soporte administrativo para el proceso de planificación académica de la facultad de ingeniería en electricidad y computación - Tama Wong, Luis Antonio (2010)
The development of the planning of academic units is an important activity within the undergraduate teaching process defined in the Quality Management System at ESPOL, since the registration process for each academic term depends directly on this planning. Until now, academic planning of the Faculty of Electrical and Computer Engineering (FIEC) has been developed using basic utility programs that do not offer enough support to the dean, area coordinators and career coordinators, in terms of collaboration among them, reference to historical data, editing of class and activity planning, and correction of schedule conflicts. This article presents a software solution based on web technologies and business process management, which increases the productivity of the actors involved in the planning of classes, schedules and activities of teachers in